2018
DOI: 10.1007/s40093-018-0225-7
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting of different organic materials using the epigeic earthworm Eisenia foetida

Abstract: Purpose The present research was conducted with the objective of exploring the vermicomposting process, which involves different stages such as building of a vermicompost station; import of a compost earthworm (Eisenia foetida); and production of vermicompost using dry grass clippings, rice straw and cow manure. The vermicompost produced can be of significant value to the end users like farmers for replacement of chemical fertilizers and procuring better prices for the organic produce using such composting mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(68 citation statements)
references
References 33 publications
5
42
2
1
Order By: Relevance
“…The carbon loss due to respiration of earthworm-associated microbes could be the reason for the decreased C:N ratio. Previous studies also suggested the transformation of C to CO 2 through microbial respiration and an increase in N content due to mineralization [53,54] The recycling of sludge through vermitechnology revealed a decreased C:Nratio (Srivastava et al, 2020) of dry grass and rice straw [55]. Scientific studies revealed the value of the C:N ratio as an indicator of compost maturity with a ratio less than 20 indicating advanced degree of stabilization [56] and <15 desirable for crop production [57].…”
Section: C:n C:p and C:s Ratiomentioning
confidence: 97%
“…The carbon loss due to respiration of earthworm-associated microbes could be the reason for the decreased C:N ratio. Previous studies also suggested the transformation of C to CO 2 through microbial respiration and an increase in N content due to mineralization [53,54] The recycling of sludge through vermitechnology revealed a decreased C:Nratio (Srivastava et al, 2020) of dry grass and rice straw [55]. Scientific studies revealed the value of the C:N ratio as an indicator of compost maturity with a ratio less than 20 indicating advanced degree of stabilization [56] and <15 desirable for crop production [57].…”
Section: C:n C:p and C:s Ratiomentioning
confidence: 97%
“…Vermicompost is rich in nitrogen, phosphorus, potassium, micronutrients and other beneficial soil microbes (nitrogen fixing and phosphate solubilizing bacteria) [31]. It is a sustainable alternative to chemical fertilizers, which is an excellent growth promoter and protector for crop and plants [13]. Different organic waste material like rice straw, dry grass, chippings, cow dung, dry leaves, rotten watermelon, papaya, pine apple, custard apple and guava has been used in preparing vermicompost biofertilizer [2,9,13].…”
Section: Methodsmentioning
confidence: 99%
“…Micro-mineral are essential for plant growth, but plants requires relatively small amount of them, hence the term micro. They include boron, chlorine, copper, iron, manganese, molybdenum and zinc [13]. Generally bio-fertilizers produced through vermicom-post method are rich in micro and macro-nutrients which are very vital in soil nutrient enrichment [9].…”
Section: Methodsmentioning
confidence: 99%
“…Vermicompost the most organic fertilizers peat-like materials, produced from various organic materials by composting process using defined species of earthworms (Ramnarain et al, 2019), Also, Vermicompost is made of finely divided particals, contains numerous nutrients in available forms it has beneficial characters as high porosity, microbial activity, good aeration and drainage, increase water holding capacity, remarkable nutrient status and buffering capacity (Pathma and Sakthivel. 2012) (Piya et al, 2018), in addition vermicompost, promote beneficial microbes, provide different microsites for microorganisms and, so enhancing soil biodiversity which consecuantly improve plant growth, and it's rich in various microbial populations like fungi, bacteria and actinomycetes (Lim et al, 2015).…”
Section: Vermicompostmentioning
confidence: 99%